From Linear to Circular: Empirical Evidence of Circular Economy Adoption and Willingness to Pay in an Indonesian Coastal City - Meylin Rahmawati; Sulistya Rini Pratiwi; Anindya Arman Putri; Rizky Agusriyanti Irna; Kartini Kartini (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
This study aims to: (1) estimate WTP and aggregate waste fee revenue potential; (2) evaluate community preferences for six CE strategies and their fiscal feasibility; (3) identify determinants of WTP using binary logistic regression; and (4) formulate an evidence-based policy portfolio to close the financing gap in Tarakan City's waste management system. Using CVM and binary logistic regression on 350 households (2024): (1) mean WTP of IDR 174,500/household/year yields IDR 3.93 billion/year aggregate (95% CI: IDR 3.60–4.26 billion) or 71% cost recovery; (2) CE strategy BCR hierarchy: reduce (∞) > reuse/recovery/sorting (1.46) > recycle (0.73) > repair (0.29); (3) Income (OR=2.14; p<0.05) and Education (OR=1.87; p<0.05) are the only significant WTP determinants — confirming the value-action gap and falsifying the information deficit model; (4) a three-level policy portfolio achieves near-full fiscal self-sufficiency (≈99.8% cost recovery) through progressive tariffs and recycling monetization.